Penerapan Asas Lex Specialis dalam Kasus Penipuan Berbasis Manipulasi Bukti Transfer Digital: Penelitian - Gabriel Regina Christian; Gousta Feriza (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This research examines the application of Article 35 of the Electronic Information and Transactions Law (UU ITE) in cases involving manipulated digital transfer receipts, as adjudicated in Decision Number 358/Pid.B/2023/PN Yogyakarta. The study is motivated by the increasing prevalence of cybercrimes involving falsified electronic data, while law enforcement practice remains inconsistent in determining whether the lex specialis provision under the ITE Law or the general fraud provision under Article 378 of the Indonesian Criminal Code (KUHP) should apply. This research addresses two main issues: the analysis of criminal elements based on trial facts, and the application of electronic evidence as well as its implications for legal certainty in enforcing the ITE Law. A normative legal research method is employed, using statutory, case, and document approaches through examination of the court judgment. The results reveal that the elements of electronic data manipulation under Article 35 of the ITE Law were actually fulfilled, but the judges applied Article 378 KUHP by treating the falsified transfer receipt merely as an auxiliary tool rather than the core of the offense. This approach creates normative inconsistency and weakens the function of the ITE Law as lex specialis. The study concludes that the enforcement of the ITE Law in digital fraud cases has not been optimized, highlighting the need for standardized digital evidence examination and judicial guidelines to strengthen legal certainty.